Scale‐dependent responses of longleaf pine vegetation to fire frequency and environmental context across two decades. (7th May 2015) - Palmquist, Kyle A.; Peet, Robert K.; Mitchell, Stephen R.; Canham, Charles
Summary Disturbance is an important driver of plant community structure in many grasslands and woodlands, and alteration of disturbance regimes can have large consequences for species richness and composition. However, the response of vegetation to disturbance may change with environmental context. We resampled a unique, nested permanent vegetation plot data set in the longleaf pine ecosystem of the southeastern USA after 20 years to determine how environmental context and fire frequency jointly influence vegetation change across multiple spatial scales (0.01–1000 m2). The magnitude of vegetation change was quantified using two different, yet complementary metrics of beta‐diversity (beta turnover measured as the proportion of species turning over and Bray–Curtis dissimilarity) and by documenting changes in species richness. We used null model analysis to explore whether communities were more dynamic over time at small spatial scales relative to larger scales. Changes in species richness, beta turnover and Bray–Curtis dissimilarity were greatest on silty, frequently burned sites, whereas sandy, less frequently burned sites remained relatively stable. The amount of change detected was scale dependent: species richness increased at larger spatial scales over time, but decreased at the two smallest spatial scales. Null model analysis revealed that beta turnover standardized effect sizes (SES) were negative and significantly different from random expectation at all spatial scales except the smallest. Thus, the magnitude of compositional change across most scales was small, despite substantial changes in species richness across time. We attribute this initial contradiction to the turnover of infrequent, low‐abundance species amidst a matrix of dominant grasses. Synthesis. In contrast to previous longleaf pine studies, we found fire frequency to be less important than environmental site conditions in predicting vegetation change. Thus, future work in this ecosystem and in other fire‐dependent grasslands and woodlands should consider not only disturbance, but also environmental context. Since species richness and beta‐diversity patterns were scale dependent, we recommend sampling vegetation across multiple spatial scales in order to comprehensively quantify changes in community structure over time. We believe this study lays the groundwork for understanding how fire and environmental filtering jointly influence vegetation dynamics across space and time in fire‐dependent grasslands and woodlands.